Feasibility of Orienteering Development in Karst Regions: Evidence from Huaxi District, Guiyang, China - Zeng Bowei (International Journal of Education and Humanities, 2026)
Orienteering is a sport characterized by distinctive training methods and a strong integration of physical fitness, cognitive skills, and environmental interaction. Since its introduction in China, orienteering has gained increasing popularity, particularly in Guizhou Province, where various comprehensive competitions have been successfully organized. However, despite Guiyang City's Huaxi District possessing significant natural and cultural advantages—such as a unique karst landform, favorable climatic conditions, rich folk traditions, tourism resources, and strong governmental support for sports development—the sustainable development of orienteering in this area still faces several challenges. These challenges include the insufficient integration of local cultural resources, inadequate risk management mechanisms, and limited promotional strategies. This study aims to analyze the feasibility and development potential of orienteering in Guiyang City's Huaxi District and to explore a development model that reflects the distinctive characteristics of Guizhou Province. A mixed-method research design was employed. The study used a literature review to examine the concept, development history, and characteristics of orienteering, along with questionnaire surveys and semi-structured interviews conducted with orienteering enthusiasts in Guiyang. The findings indicate that Huaxi District has strong feasibility for orienteering development, driven by its natural terrain, ecological environment, and policy support. Nevertheless, weaknesses were identified in cultural resource integration, safety management, and public awareness. Addressing these issues is essential for long-term development. The study implies that a localized orienteering development pathway should be established by integrating regional culture, enhancing risk management systems, and strengthening promotional efforts. These findings are expected to provide practical guidance for developing a distinctive and sustainable orienteering model in Guizhou Province